Beam quality optimization of electrically pumped VECSELs for passive modelocking - Pallmann, W. P.; Hoffmann, M.; Miller, M.; Baier, J.; Moench, H.; Dahhan, I.; Witzigmann, Bernd; Golling, M.; Barbarin, Yohan; Suedmeyer, T.; Keller, Ursula (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Fundamental mode operation along with high output power is a major challenge for an electrically pumped VECSEL (EP-VECSEL) suitable for passive modelocking. We present an experimental study on the influence of the intermediate DBR reflectivity on the beam quality and the output power of EP-VECSELs. For designs with reflectivities of 90%, 82% and 71% the highest possible power for the best achievable beam quality was 15.1 mW (M2 = 1.1, 82% device). We can demonstrate that a correctly chosen intermediate DBR reflectivity is necessary for both good beam quality and high power, and that a trade-off in power has to be accepted.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electrical pumping; Passive modelocking; Semiconductor lasers; Vertical emitting lasers